Financial sustainability of mini-grid electricity distribution companies in Uganda - Kinhonhi, Isaac Vivian (Graduate School of Business (GSB), 2019)
This study investigated the financial sustainability of electricity Mini-grids in Uganda. The challenges of sustainability of Mini-grids were recognised by Tenenbaum Bernard, Greacen Chris, Siyambalapitiya Tilak (2014) as well as Payen, Bordeleau and Young (2016), with a focus on developing countries, particularly in Asia. There is, however, no literature that was found on similar challenges in Uganda. The specific objectives of this study were to examine the profitability, liquidity, efficiency and operational sustainability of Mini-grids in Uganda. The study focused on four Mini-grids as case studies: Ferdsult Engineering Services Limited (FESL), Bundibugyo Energy Cooperative Society (BECS), Kilembe Investments Limited (KIL) and West Nile Rural Electrification Company (WENRECO). The research objective was addressed by analysing audited financial reports for the respective Mini-grids from 2010 to 2015 and other operational information published by the electricity regulator. The study established that Mini-grids in Uganda were not financially sustainable despite having steady growth in sales revenue and customer numbers. The main factors that affected the sustainability of Mini-grids include a higher growth rate in operational and maintenance costs compared to the sales revenue. In addition, operational efficiency challenges were observed, including energy losses, imprudent financial management practices and poor liquidity. These shortfalls consequently showed that the Mini-grids are not financially sustainable. Despite the fact that Mini-grids are not financially sustainable in Uganda, their benefits go beyond electricity provision. The other benefits of Mini-grids are socio-economic in nature, including support for health services and enhancement of economic activities and the livelihoods of the poor. The socio-economic benefits from access to electricity in these rural areas may far outweigh the financial limitations observed. It is therefore important that Mini-grids continue to get the necessary support until such a time as they become sustainable. It is recommended that the Government of Uganda should provide financial and operational support through subsidies or other support systems to ensure continuity of the Mini-grids and, ultimately, their financial sustainability in the medium term in order to enhance access to electricity and the knock- on benefits that come with this access. In this regard, governance and technical skills enhancement remain key in order for these -grids to move forward. Further research should establish the optimal size and internal operational parameters that will ensure the sustainability of the Mini-grids, the amount of government subsidy required and the time it would prudently take to attain sustainability.